Pengembangan Perangkat Pembelajaran berbasis Brain-Based Learning untuk Meningkatkan Hasil Belajar Siswa - Ainul Khafid (IKIP Mataram, 2016)
The purpose of this research is to produce teaching materials based on Brain-based learning that appropriate to improve student’s learning achievement on the topic of salt hydrolysis. The development models of teaching materials used 4-D models using one group pretest-posttest design. The subjects of the research were teaching materials based on Brain-based learning that tried to 30 students of XI grade MIA 1 MA Nahdhatul Ulama Sidoarjo in academic year of 2015/2016. The data-collecting techniques in this research were validation, observation, test, and questionnaire. The results showed that (1) the validity of the lesson plans, student book, worksheet, and learning achievement test were valid; (2) the readability level of student book and worksheet were good category; (3) learning feasibility were good category; (4) the students activities refers to student-centered learning; (5) majority of students gave positive response to learning process; (6) all of students achieved learning completeness criteria on aspect of cognitive, attitudes, and skills. Based on these results, it could be concluded that the teaching materials based on Brain-based learning were appropriate to improve student’s learning achievement on the salt hydrolysis topic.